Quality of Work Life and Organization Culture - Shankar, J.Vignesh (International Journal of Scientific Research and Management (IJSRM), 2014)
The Objective of this paper is to determine the quality of work life and morale of employees and their effects on organization culture. To reach the quality of work life mostly depends upon making regular attempts from an organization, which provides their employees with more opportunities so that they can be more effective in their organization. Quality in an organization is defined as an advantage, as a value, as determination of conformity and as meeting customer’s expectations. Good quality of work life is necessary for an organization to attract and to retain skilled and talented employees. Employees are the most important assets of any organizations and its success or failure depends on their qualifications and performance. In order to survive in the competitive market because of Liberalization, Privatization and Globalization and to minimize the attrition rate of employees the quality of work life initiatives are very important. Motivated employees and Satisfied customers are the backbone of any successful organizations. This paper focuses and analyzes the literature findings which involve quality of work life and predictors of employee motivational strategies.